The Role of Perfectionism in Social Anxiety Among College Students Using Social Media in Jakarta - Adiraja, Ethan Petrosmand; Agustina, Agustina (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the role of perfectionism on social anxiety in college students who use social media in the Jakarta area. Social media has become an integral part of college students' lives, but it often triggers social pressure and negative comparisons related to perfectionism. Perfectionism itself is a broad concept, and one aspect of it that has the potential to increase social anxiety is Perfectionistic Self-Presentation. This concept describes a maladaptive behavior in which individuals strive to constantly display perfection while hiding imperfections which in turn increases fears of negative social evaluation and exacerbates social anxiety in social media users. This study used a non-experimental quantitative approach with purposive sampling method. A total of 230 college students aged 18-25 years old who actively use social media for at least two hours per day became participants. Data were collected using the Hewitt and Flett Multidimensional Perfectionism Scale (HF-MPS) and the Social Anxiety Scale for Social Media Users (SAS-SMU) which have been adapted into Indonesian. The main data analysis in the form of regression tests showed a significant positive influence between perfectionism and social anxiety, with a contribution of 89.9%, while the remaining 10.1% was influenced by other factors that were not studied.